Effectiveness of Cipp-Based Evaluation Management Context, Input, Process, Product in Arabic Language Communication Extracurriculars - Wicaksono, Triadi; Anam, Syamsul; Maulana, Asep (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This article aims to describe the effectiveness of CIPP-based evaluation management (Context, Input, Process, Product) in Arabic vocabulary and communication mastery at Madrasah Aliyah Unggulan Nuris Jember. The research subjects were students and teachers of the Nuris Jember Madrasah Aliyah. This study used a qualitative research design with data collection techniques: in-depth interviews, document review, Focus Group Discussion (FGD), and (4) observation. Data analysis in this study used a qualitative descriptive analysis technique which consisted of the stages of data collection, data reduction, data presentation, and conclusion. The results of this study were obtained, namely; 1)